2019
DOI: 10.1021/acs.inorgchem.9b02302
|View full text |Cite
|
Sign up to set email alerts
|

Metal Hydride Vibrations: The Trans Effect of the Hydride

Abstract: trans-Dihydride complexes are important in many homogeneous catalytic processes. Here vibrational spectroscopy and density functional theory (DFT) methods are used for the first time to reveal that 4d and 5d metals transmit more effectively than the 3d metals influence of the ligand trans to the hydride and also couple the motions of the trans-hydrides more effectively. This property of the metal is linked to higher hydride reactivity. The IR and Raman spectra of trans-FeH2(dppm)2, trans-RuH2(PPh­(OEt)2)4, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 97 publications
2
18
0
Order By: Relevance
“…The symmetric stretching wavenumbers of 1958 cm –1 for 64 ZnH 2 and 2112 cm –1 for 202 HgH 2 are calculated from physical constants obtained from spectroscopic measurements and not determined directly. Isolated in matrix experiments and studied spectroscopically, these compounds help validate our choice of functional and basis set …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The symmetric stretching wavenumbers of 1958 cm –1 for 64 ZnH 2 and 2112 cm –1 for 202 HgH 2 are calculated from physical constants obtained from spectroscopic measurements and not determined directly. Isolated in matrix experiments and studied spectroscopically, these compounds help validate our choice of functional and basis set …”
Section: Resultssupporting
confidence: 81%
“…This expression included the nature of the ligand trans to the hydride, the character of the metal, and the overall charge of the complex. Subsequent work showed that 4d and 5d transition metals have a larger interaction between the M–H stretching modes and a marked increase in negative character of the charge gradient of the departing hydride . This increase in effective transmission of charge through the metal center is thought to explain the increased activity of ruthenium-, osmium-, rhodium-, and iridium-based trans -dihydride complexes for hydrogenation compared to their 3d metal counterparts.…”
Section: Introductionmentioning
confidence: 82%
“…A report studying the IR and Raman spectra of d 6 trans-dihydride complexes found the substitution of a hydride for deuteride resulted in changes in the charge gradient and density in these species. 48 An effect of this sort may explain the differing influence of a hydride or deuteride trans to the BH (Bridging) on the chemical shift of this proton; however, more analogous examples would be needed to support this hypothesis. Both isotopic enrichment experiments are consistent with N−H/D activation of the AB substrates and further support the peak assignments in the 1 H NMR spectrum.…”
Section: ■ Introductionsupporting
confidence: 85%
“…The Co–H/D mixture of the product also results in the splitting of the BH (Bridging) resonance in the 1 H NMR spectrum. A report studying the IR and Raman spectra of d 6 trans -dihydride complexes found the substitution of a hydride for deuteride resulted in changes in the charge gradient and density in these species . An effect of this sort may explain the differing influence of a hydride or deuteride trans to the BH (Bridging) on the chemical shift of this proton; however, more analogous examples would be needed to support this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…In this vein, recent studies have demonstrated that the osmium species are a class of versatile catalysts. For instance, several newly synthesized osmium complexes have shown to possess relevant catalytic performance in transfer hydrogenation (TH), hydrogenation (HY), as well as dehydrogenation (DHY) processes with activities comparable to or even higher than those of the ruthenium analogues. , Driven by these elegant works and the successful history of the development of their ruthenium counterparts in C–H activation chemistry, we envisioned that the careful switching of the ligand, the DG, and/or related reaction parameters might control the polarized nature of the Os–C bond through changing the coordination environment between the osmium metal and the substrate, which then tuned the reactivity and the selectivity of the Os–C species to ensure sufficient interactions of the Os–C bond with a proper coupling reagent, thus leading eventually to facile construction of ideal complex products via osmium-catalyzed C–H activation reactions. As part of our ongoing efforts, herein, we would like to disclose the first osmium­(II)-catalyzed and HOAc-assisted redox-neutral C–H activation/[4 + 2] annulation example for the synthesis of isoquinolones (Scheme b).…”
mentioning
confidence: 99%